Active tuberculosis in psoriasis patients treated with TNF antagonists: a French nationwide retrospective study. (3rd June 2016) - Guinard, E.; Bulai Livideanu, C.; Barthélémy, H.; Viguier, M.; Reguiai, Z.; Richard, M.A.; Jullien, D.; Beneton, N.; Bara, C.; Vabres, P.; Grandvuillemin, A.; Marguery, M.C.; et al.
Abstract: Background: There is limited information about active tuberculosis (TB) occurring in psoriasis patients treated with Tumor necrosis factor (TNF) antagonists. Objective: To describe the clinical characteristics of TB in psoriasis patients treated with TNF antagonists. Methods: Nationwide retrospective study of psoriasis patients having experienced TB. Cases of TB were collected via three methods: search in the national pharmacosurveillance database, questionnaire to members of the French psoriasis research group, the college of French dermatology professors. We collected demographic data, TNF antagonist used, screening for latent tuberculosis infection, median time between TNF antagonists introduction and first symptoms, tests used for diagnosing TB infection, clinical features of tuberculosis and outcome. Results: Eight centres reported 12 cases of TB between 2006 and 2014. They were nine men and three women with mean age of 49 years. All patients had adequate screening for latent tuberculosis. Three patients had stayed in endemic areas, three reported contact with a patient with TB. Tuberculosis presentation was extrapulmonary in 10 patients. Seven patients were treated with infliximab, four with adalimumab and one with certolizumab. The median time between TNF antagonist introduction and first symptoms of tuberculosis was 23.4 weeks (2–176). Six of the 12 patients had a positive direct examination and/or positive culture for Mycobacterium tuberculosis. Histological samples of affected organs taken from seven patients showed granulomatous inflammation in six, with caseating necrosis in five. Two of the 12 patients died of disseminated TB. Conclusion: This study shows tuberculosis in patients treated with TNF antagonists still occurs despite adherence to tuberculosis prevention guidelines. Prophylactic measures do not fully prevent the occurrence of tuberculosis. Rapid initiation of effective anti‐tuberculosis treatment is important even in patients with negative mycobacteriological examination presenting with suggestive symptoms and organ involvement.